Intravitreal ranibizumab in the management of acute central serous Chorioretinopathy - Nawaiseh, Ibrahim; Halawa, Ahmad; Alardah, Dina (International Journal of Clinical and Experimental Ophthalmology, 2017)
Purpose: To evaluate the efficacy of ranibizumab in hastening the recovery of acute CSCR when given immediately at time of diagnosis. Methods: In This retrospective case series, a total of 72 patients diagnosed with acute CSCR where reviewed, of which 63 received Ranibizumab at presentation. The patients were evaluated using Best corrected visual acuity, Ophthalmic examination, Optical coherence tomography (OCT) and fluorescein angiography, in addition to indocyanine green angiography and OCT angiography in some cases, at presentation, one week, one month and two months’ post injection. Results: From the total 72 patients diagnosed with acute CSCR, 63 of them received intravitreal ranibizumab and the remaining 9 patients preferred to go for observation. The mean age of patients was 41.2 year old. The ratio of male to female was 8:1. The mean BCVA at presentation was 6/15 on Snellen chart. All patients who received ranibizumab injection showed an improvement after 1 week, with a mean improvement in BCVA of two lines. Of them, 43 patients were back to BCVA of 6/6 after 2 months and showed complete resolution of sub retinal fluid. The remaining 20 patients showed an additional mean of improvement of one line (over the previous two lines) after the 2 months. Conclusion: Intravitreal ranibizumab hasten the recovery of both the BCVA and central macular thickness on OCT in acute CSCR when given immediately at presentation.